우크라이나 전쟁 발발 이후 EU의 대(對)러시아 에너지 정책 전환: 단절균형이론과 안보화 개념의 통합적 접근 - 한희진; Heejin Han (글로벌정치연구, 2025)
2022년 2월 러시아의 우크라이나 침공은 유럽을 포함한 전 세계 에너지 지형에 충격을 가했다. 유럽연합(EU)은 전체 화석연료 수입의 40% 이상을 러시아에 의존해 온 만큼, 본 전쟁은 에너지 가격 급등과 인플레이션을 초래하며 유럽의 에너지 안보 위기를 심화시켰다. 이에 대응하여 EU는 2027년까지 러시아산 에너지에 대한 의존도를 급격히 낮춘다는 목표를 설정하고 재생에너지 전환 가속화와 역내 에너지 협력 강화를 골자로 하는 REPowerEU 계획을 발표했다. 이 계획은 2014년 러시아의 크리미아 강제 합병에 대응해 EU가 채택한 에너지안보전략(EESS)과 유사성을 지닌다. 그러나 EESS 도입 후에도 EU의 대러시아 에너지 의존이 유지, 심화되어 왔다면, REPowerEU는 에너지 공급 다변화와 역내 에너지 연대를 통한 탈러시아화를 목표로 신속하게 추진되어 왔다는 점에서, EU의 에너지 정책에 단절적, 급진적인 전환이 발생했음을 알 수 있다. 본 연구는 단절균형이론과 코펜하겐학파의 안보화 이론을 접목해 우크라이나 전쟁이라는 외부적 충격에 직면해 EU의 에너지 안보 담론과 정책 대응이 어떻게 변화해 왔는지를 체계적으로 분석한다. 이를 통해 본 논문은 러시아산 에너지에 대한 의존이 지역의 안보 위협으로 안보화되면서 EU 에너지 정책에 단절적 전환이 발생한 과정을 규명한다. The Russian invasion of Ukraine in February 2022 profoundly disrupted the global energy landscape, particularly in Europe. The European Union (EU), which had relied on Russia for over 40% of its fossil fuel imports, faced a severe energy security crisis marked by soaring energy prices and inflation. In response, the EU unveiled the REPowerEU plan, which aims to drastically reduce its dependence on Russian energy by 2027 through an accelerated transition to renewable energy and enhanced intra-EU energy cooperation and solidarity. This plan bears similarities to the European Energy Security Strategy (EESS) adopted by the EU in response to Russia’s annexation of Crimea in 2014. Whereas the EU’s dependence on Russian energy persisted even after the adoption of the EESS, the launch of REPowerEU represents a radical shift toward decoupling from Russian energy sources, with a heightened emphasis on energy supply diversification and regional energy cooperation. This indicates that a punctuated and radical shift has occurred in the EU’s energy policy. This study integrates Punctuated Equilibrium Theory with the Copenhagen School’s securitization framework to systematically analyze how the EU’s energy security discourse and policy responses evolved in the wake of the external shock triggered by the Russian invasion. The analysis reveals how dependence on Russian energy was securitized as a regional threat, leading to a punctuated transformation in the EU’s energy policy.